Prevalence of risk factors for cardiovascular disease in adults living in a rural community of Nepal. - Ghimire, Manish (2020)
ABSTRACT: Background: Cardiovascular disease is a leading cause of morbidity and mortality worldwide especially in low and middle-income countries accounting for three quarters of total deaths. However, there are few studies on CVD risk factors in rural setting of Nepal. Thus, this study aimed to determine the prevalence of cardiovascular risk factors in a rural municipality of Nepal. Methods and materials: We conducted a cross-sectional study in Bethanchowk, rural municipality of Kavrepalanchowk district between April 2018 and December 2019. Adults aged 18 to 65 years were randomly selected. Data were collected using WHO-NCD Stepwise approach to surveillance questionnaires and analyzed with SPSS version 23 using chi-squared tests. Results: A total of 422 respondents were included in the study. Majority of the respondents were male (61.6%), in the age group of 45 - 65 years (57.6%), with education of below secondary level (55.2%), Brahmin ethnicity (53.8%), and agriculture (42.1%) as their main occupation. Smoking was prevalent in 25.4%, alcohol consumption in 28.4%, adequate physical activity in 99.5%, insufficient fruits and vegetables intake in 100%, obesity in 59.0% and hypertension in 27.7%. Conclusion: A high prevalence of smoking, alcohol consumption, insufficient fruits and vegetable intake, obesity and hypertension was found in this rural population suggesting higher risk of developing CVD in future. Therefore, a population wide approach is required to reduce these CVD risk factors. Keywords: Behavioral risk factors, Cardiovascular diseases, Nepal, Rural municipality.